Organic Solar Cells: Highly Efficient Organic Solar Cells Consisting of Double Bulk Heterojunction Layers (Adv. Mater. 19/2017). Issue 19 (May 2017) - Huang, Jiang; Wang, Hanyu; Yan, Kangrong; Zhang, Xiaohua; Chen, Hongzheng; Li, Chang‐Zhi; Yu, Junsheng
Abstract : A new approach to unlock highly efficient polymer solar cells is presented in article number1606729 by Chang‐Zhi Li, Junsheng Yu, and co‐workers, in which two bulk heterojunction layers with complementary optoelectronic properties are vertically connected via a stamp‐transfer method, and sandwiched between one set of cathode and anode for enabling over 12% power conversion efficiency.